Performance of groundnut (Arachis hypogaea) cultivars for higher productivity in hilly ecosystem - ANSARI, M A; CHOUDHURY, B U; ROY, S S; SHARMA, S K; SINGH, I M; SINGH, A L; PRAKASH, N (The Indian Journal of Agricultural Sciences, 2020)
Low productive cereals (rice and maize/mixed cropping) in the Jhum degraded abiotic stressed soils (from acidity and moisture deficit) of rainfed hilly ecosystem of Northeast India (NEI) restrict jhumias socio-economic upliftment. Shift in cropping pattern to stress-tolerant groundnut cultivars may provide an option in such a situation. We evaluated the performance of 26 improved cultivars of groundnut for four consecutive years (2013-2016) in terms of suitable agronomic and physiological traits for higher productivity in such soils under rainfed hilly ecosystem of NEI (Manipur) and compared their performances with one popular local check (JL-24). Few improved cultivars (GG-21, TG 37-A, GG-11, TKG-19-A, ICGV-86590 and ICGS-76) yielded significantly (P